Effect of Plasmonic Nanoparticles on the Electric Field Strength to Improve Performance of Single Crystalline Solar Cell - Al-Karawi, Samah Mohammed; Altemimi, Mohammed Fawzi Mohammed (Al-Nahrain Journal for Engineering Sciences, 2019)
The effect of metal nanoparticles (MNPs) on the electric field strength and distribution for improvement solar cell performance is investigated and simulated. By manipulating the properties of nanoparticles, distribution of the electric field was altered. In this paper, classical solar cell (p-n junction) and improved structure (add an extra layer of SiO2 and gold nanoparticles on the top of p-n junction) is simulated. Different sizes of NPs, thickness of SiO2 sublayer, and spacing distance between NPs is done to improving the electric field and showing plamonic effect. Gold NPs deposition on single crystalline silicon solar cell is modelled by COMSOL 5.2 2D, Electromagnetic wave propagation in the frequency domain with periodic boundary conditions. The best wavelength found in our work is 550 nm. The electric field enhances when the size of NPs increases but it must be limited. When gold NPs are deposited on the SiO2 sublayer, the plasmonic effect appears due to decreasing the refractive index. Moreover, separation distance between NPs affect the electric field enhancement by manipulating the number of NPs, the distance decreases and the plasmonic interaction appears.